Secure Data Mobility in Cloud Computing for e-Governance Application - Paudyal, Ramesh; Shakya, Subarna (Journal of Engineering Technology and Planning, 2021)
Due to the rapid technological advancement, traditional e-government systems are getting obsolete because of their inherent limitation of interoperability and accessibility to the highly secured and flexible e-governance services. Migration of such systems into highly secured cloud governance architecture will be a long-term viable solution. However, the adoption of distributed cloud computing has created operational and security challenges. This research work aims to bridge the gap between traditional and cloud-based e-Government systems in terms of data security based on confidentiality, interoperability, and mobility of data among distributed databases of cloud computing environments. In this work, we have created two organization databases by the use of AWS EC2 instances and classified the data based on the Risk Impact Level (RIL) of data by the use of the Metadata Attribute Value (MAV) function. To enhance further security on classified data, we take appropriate security action based on the sensitivity of the data. For the analysis purpose, we implemented different security algorithms, i.e. AES, DES, and RSA in the mobility of data between two distributed cloud databases. We measured the encryption and decryption time along with the file size of data before and after classification. AES performed better while considering the encryption time and file size, but the overall performance of RSA was better for smaller file sizes. Finally, the performance of the data mobility between two distributed clouds databases was analyzed while maintaining the sensitivity level of the data.